Local food policy: implementation of food initiatives from the national level to the level of territorial communities of Kharkiv region - Nekhaienko Oksana (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2023)
The article is devoted to the analysis of food policy in the Kharkiv region. In addition, the article examines certain aspects of the national policy aimed at preventing the food crisis in the conditions of war. The author briefly examines the main problems and challenges faced by agriculture and the food sector in wartime conditions. The article highlights the main measures aimed at ensuring equal access to food products in wartime and the steps taken for this purpose at different levels: national, regional and in individual communities of the Kharkiv region. In more detail, the article examines the role of local authorities and public initiatives in improving food policy, as they allow not only to ensure food security, but also to involve internally displaced persons in economic activities. The author states that the prospects of food policy in the Kharkiv region are dependent on many factors, in addition to the actual course of the military conflict. The article concludes about the special importance of the following factors: strengthening the defense capability and security of agricultural facilities, transport routes; increasing the efficiency and transparency of the mechanisms of state regulation of food prices, control over the quality and safety of food products, prevention of speculation and abuse; expanding the scope and variety of state support to national food producers; development of international cooperation and integration into the European and world market; support and development of public organizations, volunteer movement, social entrepreneurship, local initiatives and projects that contribute to the provision of food and support to the needy; raising the level of education, culture, awareness and responsibility of the population regarding food security.